Outcomes of Enhanced Recovery After Surgery (ERAS) in Gynecologic Oncology—A Systematic Review and Meta-analysis. Issue 4 (April 2021) - Bisch, S. P.; Jago, C. A.; Kalogera, E.; Ganshorn, H.; Meyer, L. A.; Ramirez, P. T.; Dowdy, S. C.; Nelson, G.
Abstract : (Abstracted from Gynecol Oncol 2021;161:46–55) Enhanced recovery after surgery (ERAS) pathways aim to reduce length of stay (LOS) and complications postoperatively and have demonstrated substantial benefit in these metrics across a wide range of surgical fields. Despite this evidence, the adoption of ERAS in gynecologic oncology on a global scale remains low, and some centers show minimal improvement in clinical outcomes after ERAS adoption.